Urinary calcium to creatinine ratio to predict preeclampsia and use of calcium supplementation to prevent preeclampsia - Munge, Anjali M.; Satia, Meena N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Incidence of preeclampsia is around 5-10% of all pregnancies, and in developing countries around 4-18%. There is hypercalciuria during normal pregnancy, while pre-eclampsia is associated with hypocalciuria and low urinary calcium to creatinine ratio. Low calcium intake has been hypothesized to cause increase in blood pressure. The present study was carried out to investigate significance of urinary CCR in prediction of preeclampsia & role of calcium supplementation in reducing preeclampsia. Methods: 100 pregnant patients were divided into two groups, 50 cases and 50 controls. A spot urine sample was collected for estimation of CCR at around gestational age of 20-24 weeks. Cases were given 2 gm of calcium supplementation. Controls were 1 gm calcium .Then at each visit both the groups, were evaluated for symptoms of preeclampsia. Urinary calcium to creatinine ratio was calculated and those with ratio <or = 0.04 were considered test positive and those with ratio of >0.04 were considered test negative. Results: The test (urinary CCR <= 0.04) was positive in 16 patients, 9 developed preeclampsia. The test was negative test (urinary CCR >0.04) in 84 patients and in those only 5 developed pre eclampsia. Urinary CCR had sensitivity of 63.63%, specificity of 94.87%. Out of 50 cases, only 3 developed preeclampsia. Out 0f 50 controls, 11 developed preeclampsia. Conclusions: Urinary CCR between 20-24wks of gestation will be an effective screening method for impending pre-eclampsia. Calcium supplementation (2gms/day) can help in prevention of preeclampsia.